Impact of Plastic Waste on the Marine Biota - Shahnawaz, Mohd.; Sangale, Manisha K.; Daochen, Zhu.; Ade, Avinash B.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This contributed volume focuses on the effects of macro, meso, micro, and nanoplastic waste on marine biota. It discusses the threats posed by plastic waste on the flora and fauna in the marine environment. This book will help in understanding different aspects of plastic waste generation, its transportation with different natural and anthropogenic ways, its accumulation at the seacoast, and its impact on marine biota. The book also suggests strategies for saving marine life from threats posed by plastic waste and presents methods to reduce its generation using different strategies. This book is of interest to teachers, researchers, climate change scientists, capacity builders, and policymakers. It also serves as additional reading material for undergraduate and postgraduate students of Ecology, Botany, and Environmental Sciences.
Chapter 1. Degradation of plastic waste in the marine environment -- Chapter 2. Generation and management of macro-plastic waste -- Chapter 3. Generation and management of microplastic waste -- Chapter 4. Biodegradation of the Macro-plastic Waste using Microbial approach -- Chapter 5. Strategies to cope with the plastic pollution in the sea -- Chapter 6. Mitigation of the plastic pollution in the marine environment to conserve the marine biota: An overview -- Chapter 7. Regulations To Minimize The Entry Of Plastic Waste Into The Oceans -- Chapter 8. Recent trends to address plastic waste at the global level -- Chapter 9. Mitigation of the micro and nano-plastic using phycoremediation technology -- Chapter 10. Impact of the COVID-19 Outbreak on The Generation of Plastic Waste -- Chapter 11. Entry of macro, micro, and nano-plastic in the food chain and their impact on marine life (from source to sink) -- Chapter 12. Effect of meso, micro, and nano-plastic waste on the benthos -- Chapter 13. Impact of Plastic Waste on the Coral Reefs: An Overview -- Chapter 14. Ecotoxicological impact of macroplastic to nanoplastic on marine macrophytes -- Chapter 15. Ecotoxic effects of the plastic waste on marine fauna: An overview -- Chapter 16. Plastic waste enhancing the pathogenicity of the pathogens to cause diseases in the marine biota.-.
Keywords: Refuse and refuse disposal; Environmental management; Sustainability; Waste Management/Waste Technology; Environmental Management; Sustainability